Diversifikasi Olahan Ikan Lele Sebagai Alternatif MPASI Guna Pencegahan Stunting Di Kabupaten Jember - Ayu Joyana Sri Hartatik; Yeni Sutrianingsih; Dian Aris Monna; Elly Nurhandayani; Dewi Deniaty Sholihah (Institut Teknologi dan Bisnis Semarang, 2024)
Stunting is a chronic nutritional problem caused by prolonged inadequate nutrient intake, leading to growth impairment in children aged 0-59 months. Complementary feeding, known as MPASI in Indonesian, refers to the introduction of solid foods and liquids to infants aged 6 to 24 months. In Indonesia, stunting is a significant health issue that cannot be ignored. According to the National Nutrition Status Survey (SSGI) data, the prevalence of stunting in Indonesia reached 21.6% in 2022, ranking fifth globally and second in Southeast Asia. Specifically, Jember Regency holds the first position in East Java, with a staggering rate of 34.9%. The occurrence of stunting in children can be influenced by inappropriate quality and timing of MPASI provision. One potential intervention to address the stunting problem in Jember Lor Subdistrict, Patrang District, Jember Regency, East Java Province, is to provide training on processed MPASI products, such as catfish nuggets. Catfish is a type of fish rich in protein and amino acids. Lysine, an amino acid found in catfish, can positively impact child growth, tissue repair, antibody production, and calcium absorption. The community engagement activities in this initiative utilize a mass communication approach through education and training sessions. The promotion of balanced nutritious food and training on local food processing, specifically catfish nuggets, aims to prevent and control stunting conditions in Jember Lor Subdistrict, Patrang District, Jember Regency, East Java Province.